Synthesis of a Co3V2O8/CNx hybrid nanocomposite as an efficient electrode material for supercapacitors. (17th March 2021) - Mishra, Ranjit; Panda, Prajnashree; Barman, Sudip
Abstract : Cobalt vanadium oxide/carbon nitride composite (Co3 V2 O8 /CN x ) was synthesized by solvothermal method. This Co3 V2 O8 /CN x composite was applied for asymmetric supercapacitor application. Abstract : Development of electrode materials for electrochemical energy storage is of great importance because of the growing energy demand. Supercapacitors are important energy storage devices because of their high power density and long cycle life. In this work, we report a simple solvothermal method to synthesize a cobalt vanadium oxide/carbon nitride composite (Co3 V2 O8 /CN x ) for superior supercapacitor performance. The composite shows a high capacitance of 1236 F g −1 at a current density of 1 A g −1 and a good cyclic stability of nearly 87% after 4000 galvanostatic charge–discharge (GCD) cycles. Furthermore, the electrochemical performance of Co3 V2 O8 /CN x is 33.18% higher than that of Co3 V2 O8 suggesting that the presence of carbon nitride in Co3 V2 O8 /CN x enhances its electrochemical performance. The asymmetric supercapacitor (ASC) was assembled using Co3 V2 O8 /CN x and activated carbon (AC) as positive and negative electrodes respectively. The ASC shows a specific capacitance of 131 F g −1 at a current density of 0.5 A g −1 and it maintained a high energy density of 40.83 W h kg −1 at a power density of 385.18 W kg −1 with a cell voltage of 1.5 V. The uniformly grown nanoparticles of the composite and the synergistic interaction between Co3 V2 O8 and CN x provide high specific capacitance along with an increase in the rate of capacitance retention which suggests that Co3 V2 O8 /CN x can be a suitable material for application in hybrid energy storage devices.